Implementation of Structured Benefit-Risk Assessments in Marketing Authorization Applications: Lessons Learned. (November 2016) - Wang, JuAn; Wolka, Anne; Bullok, Kristin; Anglin, Greg; Radawski, Christine; Noel, Rebecca
Background: A recent publication from Eli Lilly and Company provided guidance on incorporation of a structured benefit-risk assessment framework into Section 2.5.6 of the Clinical Overview of marketing authorization applications. Because a template alone cannot deliver a judicious benefit-risk evaluation, the purpose of this manuscript is to present lessons learned and practical approaches that pharmaceutical companies (sponsors) can apply in developing holistic benefit risk assessments of medicinal products for their marketing authorization applications. Methods: Benefit-risk scientists at Eli Lilly and Company facilitated use of a structured benefit-risk assessment in Section 2.5.6 of the Clinical Overview for a number of marketing authorization applications submitted to regulators between 2013 and the 2016. Based on our experiences in implementing the approach described in the publication by Wolka et al, we have identified commonalities that contributed to successful implementation. Results: The 3 key learnings from the authors' experience are to (1) use a cross-functional team approach; (2) employ a process that lends to the objectivity and efficiency of benefit-risk assessments; and (3) leverage data visualizations for clear and concise communication of benefit-risk information. Conclusions: Sponsors can apply these approaches to incorporate benefit-risk assessments into their marketing authorization applications. Further shared learnings and benchmarking among the pharmaceutical industry will be necessary to further advance the science and practice of benefit-risk assessment.